2021
DOI: 10.1128/spectrum.01546-21
|View full text |Cite
|
Sign up to set email alerts
|

Oleate Hydratase (OhyA) Is a Virulence Determinant in Staphylococcus aureus

Abstract: The oleate hydratase protein family was discovered in commensal bacteria that utilize host unsaturated fatty acids as the substrates to produce a spectrum of hydroxylated products. These hydroxy fatty acids are thought to act as signaling molecules that suppress the inflammatory response to create a more tolerant environment for the microbiome. S. aureus is a significant human pathogen, and defining the mechanisms used to evade the immune response is critical to understanding pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…These results were validated by constructing strain PDJ171 (Δ geh ), a derivative of wild-type strain AH1263 that was constructed to contain an unmarked deletion of the geh gene coding sequence ( 20 ). The production of extracellular a15-LPG was measured in strains AH1263/pPJ480, PDJ171 (Δ geh )/pPJ480 containing the empty vector, and strain PDJ171 (Δ geh )/pGeh programed to express geh driven by the sarA promoter ( Table S1 ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…These results were validated by constructing strain PDJ171 (Δ geh ), a derivative of wild-type strain AH1263 that was constructed to contain an unmarked deletion of the geh gene coding sequence ( 20 ). The production of extracellular a15-LPG was measured in strains AH1263/pPJ480, PDJ171 (Δ geh )/pPJ480 containing the empty vector, and strain PDJ171 (Δ geh )/pGeh programed to express geh driven by the sarA promoter ( Table S1 ).…”
Section: Resultsmentioning
confidence: 96%
“…The geh gene was amplified by PCR using primers designed for Gibson Assembly cloning into NdeI and HindIII digested pET28a to obtain pPJ628 with a carboxy-terminal His tag used for E. coli expression and purification of proGeh and mGeh. These His-tagged constructs were then cloned into pPJ480 at the NcoI and HindIII sites to derive plasmid pPJ630 for expression in S. aureus driven by the sarA promoter ( 20 ). Plasmids were rendered transformable into normal S. aureus strains by passing them through strain RN4220.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most highly downregulated gene in SH10001st-2 encodes an iron compound transporter, SmpB ( Table 5 ), and there were 9 iron/heme transport-associated genes that were upregulated (e.g., isdC , isdG , srtB , and heme permeases) ( Table S1 and Table 5 ). A gene encoding oleate hydratase, which is a virulence factor that promotes immune evasion by modifying host fatty acids provided by secreted lipases [ 27 ], was also downregulated ( Table 5 ). We note that these gene expression patterns were inconsistent with a strictly upregulated virulence response interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxylated form does not further convey toxicity and is not incorporated into the phospholipid membrane but is rather exported into the outer environment [ 13 ]. Recently, it was shown that OhySa are able to convert host cis - 9 unsaturated fatty acids to their 10-hydroxy derivatives in human serum and at the infection site in a mouse neutropenic thigh model, suggesting that OhySa could play a role in immune modulation in S. aureus pathogenesis [ 14 ]. Furthermore, fatty acid hydratases have been reported to be involved in stress responses of microorganisms.…”
Section: Introductionmentioning
confidence: 99%